Examining the Virtual Needs of Senior High School Headteachers in the Central Region of Ghana Amid Covid-19 - Dampson, Dandy George (Journal of Management Policy and Practice, 2022)
In the era of COVID-19, school leaders require special skills and abilities to navigate their administrative roles. However, literature seems unclear on the virtual needs of Senior High School (SHS) headteachers in this era of COVID-19. Therefore, this study investigated the virtual needs of SHS headteachers in the Central Region of Ghana. The explanatory-sequential mixed method design was adopted, where 187 headteachers were conveniently and purposively sampled for the study (quantitative phase=180; qualitative phase=7). A researcher-designed questionnaire and semi-structured interview guide were used for data collection. The quantitative data were analysed using means and standard deviation, while the qualitative data were analysed thematically. The study found that headteachers possessed low virtual administrative skills and abilities in performing their duties. The study concluded that low virtual skills of the headteachers could be caused by the over reliance on the traditional method of educational administration practiced in most Ghanaian SHSs prior to the pandemic. Therefore, headteachers require purpose-driven training in virtual administrative skills and abilities in order to perform their duties.